PERANAN HUKUM ADAT DALAM PENYELESAIAN TINDAK PIDANA - Iman Hidayat (Jurnal LEX SPECIALIS, 2012)
Abstract The process of settlement customs violations carried out by traditional institutions that act as customary justice be gradual manner. In case of violation of customs which are lightweight (small donation) is usually customary court proceedings start after a report from the litigants either in writing or verbally, then if the customary court convened and the decision has been generated, then the litigant parties are given time to think for 3 days to determine the attitude of accepting or rejecting Key Note : Customary law, criminal